(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The current study is aimed at putting the light on the suicide, its prevention strategies and crisis management. Mental health is anindivisible part of public health and significantly affects countries and their human, social and economic capital. Mental health is notmerely the absence of mental disorders or symptoms but also a resource supporting overall well-being and productivity. Positive mentalhealth is a state of well-being in which the individual realizes his or her own abilities, can cope with the normal stresses of life, canwork productively and fruitfully and can contribute to his or her community. This mental capital is vitally important for the healthyfunctioning of families, communities and society. Suicide is a complex human behavior with multiple interacting determinants.Clinicians and practitioners often face difficulties in assimilating the evidence base for suicide prevention interventions, evaluating theireffectiveness and decoding the best practice elements of each approach. In this article, we do not aim to provide an exhaustive coverageof every approach. Instead, we provide an overview of the following eight major suicide prevention interventions: awareness programs,screening, gatekeeper training, and access to means restriction, follow-up care, hotlines, media strategies, pharmacotherapeutic andpsychotherapeutic approaches. Although a number of approaches hold promise, there are difficulties in ascertaining the effectiveelements under each of them. Innovative research designs are needed to address this knowledge gap as it will facilitate optimal allocationof resources for suicide prevention.